Effect of Behaviour Cognitive Therapy on Self Pricing Levels in Human Patients Immunodeficiency Virus - Ramayanti, Eva Dwi; Lutfi, Lutfi Irham; Sulistyawati, Wiwin (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Human Immunodeficiency Virus is a virus that lowers human immunity by killing or destroying cells that play a role in immunity so that the body's ability to fight infection decreases. Of the 30 HIV sufferers in KDS Friendship Plus Kediri, 100% experienced a decrease in self-esteem. The purpose of this study was to determine the effect of cognitive behavior therapy on self-esteem in HIV patients at KDS Friendship Plus Kediri. The research design was pre-experimental one-group pre-test-post-test design. The population in this study were 32 respondents who were taken using purposive sampling technique, obtained a sample of 30. Data analysis using the Shapiro-Wilk data normality test showed that the p value before and after therapy had increased self-esteem, so it could be concluded that there was an effect of Cognitive Behavior therapy on self-esteem in people with HIV. Based on the Wilcoxon signed rank test, p value <0.05, which means that there is an effect of cognitive behavior therapy on self-esteem in HIV sufferers at KDS Friendship Plus Kediri.